The Intervention of Prenatal Gentle Yoga in Reducing Leg Swelling in Mother “I” G4P3A0 through the Utilization of a Digital Module - Rahmadina Nurhanijah; Widya Putriastuti; Rei Anggita; Karwati (STIKes Budi Luhur Cimahi, 2026)
The third trimester of pregnancy is often accompanied by physiological complaints such as leg swelling, which is caused by uterine pressure and hormonal changes. Non-pharmacological interventions like prenatal gentle yoga have the potential to reduce such discomforts. The use of digital modules can also enhance the effectiveness of education and the involvement of pregnant women. This research employed a descriptive case study with a comprehensive midwifery care approach. The subject was Mrs.